Effects of Deficit Irrigation and Intercropping of Dry Beans with Two African Leafy Vegetable Crops on Growth and Yield - Boitumelo Patience Lekgoathi; Pholosho Mmateko Kgopa; Puffy Soundy (Agronomy)
The instability between water demand and availability is making it challenging to cultivate viable, sustainable crops. To address this, improved irrigation scheduling regimes need to be adopted, focusing on full crop water requirements to determine optimal water allocation. This study aimed to identify suitable intercropping combinations of leguminous dry bean plants with indigenous African leafy vegetables (specifically cleome gynandra and cucumis myriocarpus) that could enhance interactions with regulated deficit irrigation. The experiment was designed in 3 (irrigation levels: 100%, 75%, and 50%) × 5 (three monocrops and two intercrops) split plot arrangement within a randomized complete block design (RCBD), replicated three times across four growth stages. The study was designed to rigorously assess the effectiveness of two intercrops compared to three monocrops, each cultivated under varying irrigation levels of 100%, 75%, and 50%. There was an increase in selected gaseous parameters, such as stomatal conductance and photosynthesis rates when dry beans were intercropped with cucumis myriocarpus and subjected to 75% deficit irrigation during the mid-pod stage of the dry bean. In contrast, decreased gaseous parameters were noted under a 50% deficit irrigation across all dry bean growth stages, which also negatively affected the growth of African leafy crops. Regarding yield, an inverse relationship was observed between the crops. The yield of dry beans significantly increased under 75% irrigation during the mid-pod stage. Meanwhile, yields of cucumis myriocarpus increased under both 75% and 100% irrigation levels during the early-pod stage of the dry beans, which corresponded to the vegetative stage of the two African leafy crops. In conclusion, regulating irrigation under 75% deficit irrigation during the mid-growth stage is recommended as an ideal irrigation level for intercropping dry beans with cucumis myriocarpus, and this can potentially save 25% of water.